Security and trust management : 11th International Workshop, STM 2015, Vienna, Austria, September 21-22, 2015, Proceedings /: 11th International Workshop, STM 2015, Vienna, Austria, September 21-22, 2015, Proceedings. (2015) - Unknown
No abstract available